Relasi Perkawinan Katolik dalam Perspektif “Aku-Engkau” Martin Buber - Fransiskus Dose; Marselinus Langgor; Felix Riondi Sugar; Adelberto Wili Boko (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze Catholic marriage in the perspective of Martin Buber's dialogical philosophy, particularly the concept of “I-Thou,” as an integrative and applicable approach to building family life. Catholic marriage is understood as a sacrament that is monogamous and indissoluble, based on the Holy Scriptures, Church teachings, and the Code of Canon Law. However, various contemporary challenges such as communication crises, technological developments, and internal family conflicts demand a renewal of the way of understanding husband-wife relationships in a more dialogical and personal manner. This study uses a qualitative method with a literature approach, descriptive-analytical in nature, through content analysis and hermeneutics of relevant primary and secondary sources. The results of the study show that the integration of the “I-You” concept in Catholic marriage affirms the husband-wife relationship as an encounter between subjects who are equal, dialogical, and reciprocal. This model places marriage as a responsibility for unity, a practice of dialogue for the bonum coniugum, and a communion that reaches its peak in a relationship with God, so that sacramental teachings are concretely realized in the dynamics of family life.